ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS WAKTU PROYEK DAN DAMPAKNYA TERHADAP EFEKTIVITAS BIAYA PROYEK KONSTRUKSI (STUDI KASUS: PT PAN PASIFIC NESIA SUBANG – JAWA BARAT) - Lailan Tawila Berampu (Universitas Medan Area, 2014)
The parameter of the success of a project can be seen through the effectivenes of time and cost and the quality produced. Several previous studies showed that the factor causing the achievement of the effectivenes of time and cost is the labor, materials and equipment, but, in general, a project has problem with the time and cost due to the incident of work delays and cost increases. The same thing also happens to the construction project that becomes the case discussed in this study. In this project, the lengthening of project completion time occured because of work delay that time effectivenes could be achieved that the cost effectiveness was not achieved either. Tne problem discussed in this study was what factors that influenced the effectiveness of time and cost in a construction project. The samples for this study were all of the project activities which belonged to the critical paths or condition. The data obtained were analyzed through Critical Path Method (CPM) and Path Analysis. The result of this study showed that (1) simultaneously, labor, materials, and equipment had positive and significant influence on the effectiveness of time, (2) partially, labor had positive and significant influence on the effectiveness of time, (3) partially, materials had positive and significant influence on the effectiveness of time, (4) partially, equipment did not have significant influence on the effectiveness of time, (5) simultaneously, labor, materials, equipment and effectiveness of time had positive and significant influence on the effectiveness of cost, (6) partially, labor did not have significant influence on the effectiveness of cost, (7) partially, materials did not have significant influence on the effectiveness of cost, (8) partially, equipment did not have significant influence on the effectiveness of cost, (9) simultaneously, the effectiveness of time had positive and significant influence on the effectiveness of cost, (10) the direct influence of labor was bigger than the indirect influence of labor, (11) the indirect influence of materials was bigger than the direct influence of equipment, and (12) the indirect influence of materials was bigger than the direct influence of equipment.